Your answer is -43/6
1/12(4+6x3)-9
=1/12(22)-9
=11/6-9
=11/6-54/6
=-43/6
simplify to 1 hour which will be 6 minutes in 1 hour
in 3 hours it will be 18 minutes
Answer:
36
Step-by-step explanation:
Your equation states y = 4(-1) + 3
Since the parentheses touch the number 4 which means you multiply, we will start with that first.
4 × -1 or 4(-1) (it means the same thing) would be -4
Now let us combine the equation.
y = -4 + 3
The addition property is included now,
-4 + 3 = -1
Therefore, your answer would be y = -1
Hope this helped! :D